Understanding COVID-19 vaccine hesitancy in Malaysia: Public perception, knowledge, and acceptance - Nurul Azmawati Mohamed; Hana Maizuliana Solehan; Mohd Dzulkhairi Mohd Rani; Muslimah Ithnin; Mahalecthumy Arujanan (Public Library of Science, 2024)
Indexed by WOS/Scopus/ERA